Data Mining Algorithm and New HRDSD Theory for Big Data - Pandey, Kamlesh Kumar; Shukla, Diwakar; Milan, Ram (International Journal of Computer Sciences and Engineering, 2025)
In a present time data is king for any organization. IT industry or any organization is based on data for making any type of decision like how to grow on the organization, market analysis, and consumer relationship analyses so on. In Present time data characters are changes in form of data to big data. Data is very helpful for making the decision for any organization through data mining. Big Data mining is the process of extract interesting knowledge from huge streams based databases, which hold characteristics of Big data volume, variability, velocity, variability, value, veracity, and visualization. When applying to data mining algorithm in the big dataset it gave some useful information and some not because our data mining algorithm is can’t handle all characteristics of big data at a time. This paper presented to how to data converted tradition to big data, basic characteristics of big data, suitable big data mining algorithm. We can also propose HRDSD theory for Big data mining which is useful on developing new big data mining algorithm and framework